Model-Based Tool-Assistance for Packet-Filter Design and its Future - Kaur, Gurvinder; Panda, Dr. S.N.; Dhaliwal, Dr. Dalvinder Singh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Firewall is a device that secure the private network from unauthorized access. Model based Â tool assistance Â facilitate the design task and has contribute to the correctness of the filters. But the model based tool assistance approach is design time only does not manage actions at run time. So we shall propose model on run time auditing architecture to detect the attack while packet filtering in firewall technology. It is usually based on the log-files of the packet-filters.